INSTAGRAM SEBAGAI MEDIA PROMOSI DALAM MENINGKATKAN JUMLAH PENJUALAN PADA A.D.A SOUVENIR PROJECT - Indita Dewi Aryani; Dita Murtiariyati (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
Hootsuite Social trends 2021 stated that Instagram was the first position as the most effective of social media platform to promote business. Even the survey showed that Instagram had a high penetration to market as 70%. Based on the information, there are many businesses interested to use Instagram to promote their products. One of the businesses used Instagram is A.D.A Souvenir Project. The purpose of this study was to determine the role of Instagram as a promotional medium to increase the number of sales on A.D.A Souvenir Project. The sampling technique used was purposive sampling. This research method was descriptive with a qualitative approach. The data were collected by conducting interviews and documentation. The informants were the owner, HRD and employees. The results of this study showed that the A.D.A Souvenir Project has utilized Instagram as a means of promotion media well. The results showed that, (1) There are four factors that determine A.D.A Souvenir Project choosing Instagram. The factors are Instagram as (a) a medium of relations, (b) publicity, (c) promotion, (d) market research. (2) The promotional activities through Instagram used various interesting features, namely (a) stories, (b) ads, (c) reels, (d) live, (e) Hashtags, (f) feeds, (g) Quizzes and polls. (3) The implication of Instagram in A.D.A Souvenir Project is having a good impact on increasing business both quality and quantity.